Hidup Benar Menurut Kitab Amsal dan Implikasinya bagi Pendidikan Kristen Masa Kini - Ragil Kristiawan; Eunike Eka Putri (STT Pantekosta Jakarta, 2025)
21st-century Christian education faces a critical dichotomy between the demand for academic excellence and the mandate for character formation, exacerbated by the currents of globalization. This research stems from the urgent need for a theological foundation and pedagogical framework that can integrate faith and knowledge. Using a literature study method with a descriptive-analytical approach to the text of the Book of Proverbs, this research aims to: first, identify the constituent elements of the concept of